Eficiência técnica e heterogeneidade tecnológica na agropecuária brasileira - Silva, Felipe Pinto da (2017)
This thesis analyzes the technological differences in agricultural production between municipalities located in the great Brazilian regions, with a special attention on the Brazilian Northeast. As methodological support was utilized the meta-frontier model, proposed by Battese, Rao and O’Donnell (2004) and O’Donnell, Rao and Battese (2008) to answer how these regional differences influence the efficiency of production and like this spatial heterogeneity impacts on municipalities’ technical efficiency (TE). The analysis was divided into two models. The first one proposes to analyze and identify the technological differences in agricultural production between the municipalities located in the Brazilian regions, except in the North region, for methodological reasons. On the other hand, the second one searches for the technological differentiation of agricultural production in the semi-arid and non-semiarid regions of the Northeast. For present thesis, the hypothesisis is the existence of a process of technological heterogenization of the Brazilian rural production and that this differentiation affects the level of TE of agricultural production between different regions of Brazil and within the same region as well. It was found that this hypothesis proved to be true for both models. The Model 1 revealed that the production technology practiced in the municipalities located in the South and Center-West regions are more advanced. Regarding the Model 2 indicated that the non-semiarid has the highest average TE with reference to the meta-frontier, when compared to the semiarid region.